EXTH-01. A SYNGENIC MOUSE MODEL TO STUDY THE EFFICACY OF KETOGENIC DIET IN HIGH GRADE GLIOMAS. (11th November 2019) - Salmaggi, Andrea; Vasco, Chiara; Rizzo, Ambra; Padelli, Francesco; Zucca, Ileana; Pellegatta, Serena; Massa, Giorgio; Fariselli, Laura; Bruzzone, Mariagrazia; Ciusani, Emilio
Abstract: Glioblastoma multiforme is the most malignant subtype of brain tumor. Despite multimodal treatment (surgical resection and chemo/radiotherapy) the prognosis remains unsatisfactory. Based on the Warburg hypothesis, ketogenic diet (KD) has been suggested in the treatment of GBM. The syngenic, orthotopic GL261 mouse glioma model was used to evaluate the effects of KD on 7T magnetic resonance imaging/spectroscopy and metabolic response of the tumor to diet. Mice were injected with 10^5 GL261 cells into the caudate nucleus. Following implantation, animals were fed standard chow for five days then were randomly assigned to standard diet or ketogenic diet. 18 days after diet start, mice fed at KD displayed significantly higher plasmatic levels of ketone bodies. Mice fed with KD survived longer than those fed with standard diet (p< 0.05). Decreased concentrations of gamma-aminobutyric acid, N Acetyl Aspartate and N-acetylaspartylglutamate were found in tumor tissue after 9 days from the beginning of the KD diet while a huge increase in beta-hydroxybutyrate (bHB) was detected in tumor tissue as compared to normal brain. The addition of bHB at various concentrations to low-glucose culture medium did not significantly improve GL261 in vitro growth suggesting that this cell line has a limited ability to use bHB as a carbon source. The accumulation of bHB in the tumor tissue in KD fed mice, may suggest either elevated uptake of/release of bHB by tumor cells or inability of tumor cells in this context to use it in mitochondrial metabolism; the latter hypothesis is supported by the observation that GL261 cells did not display an increase in in vitro proliferation when exposed to bHB. The far less evident peak of bHB at MRI spectroscopy in the healthy brain tissue of KD fed mice, on the other hand suggests that normal brain is able to use bHB as energy source.